Multi-decadal reduction in glacier velocities and mechanisms driving deceleration at polythermal White Glacier, Arctic Canada - LAURA I. THOMSON; LUKE COPLAND (Journal of Glaciology, 2017)
Annual and seasonal surface velocities measured continuously from 1960 to 1970 at White Glacier, a 14 km long polythermal valley glacier spanning ~100–1800 m a.s.l., provide the most comprehensive early record of ice dynamics in the Canadian Arctic. Through comparison with differential GPS-derived velocity data spanning 2012–16, we find reductions in mean annual velocity by 31 and 38% at lower elevations (600 and 400 m a.s.l.). These are associated with decreased internal ice deformation due to ice thinning and reduced basal motion likely due to increased hydraulic efficiency in recent years. At higher elevation (~850 m a.s.l.) there is no detectable change in annual velocity and the expected decrease in internal deformation rates due to ice thinning is offset by increased basal motion in both summer and winter, likely attributable to supraglacial melt accessing a still inefficient subglacial drainage system. Decreases in mass flux at lower elevations since the 1960s cannot explain the observed elevation loss of ~20 m, meaning that ice thinning along the glacier trunk is primarily a function of downwasting rather than changing ice dynamics. The current response of the glacier exemplifies steady thinning, velocity slowdown and upstream retreat of the ELA but, because the glacier has an unstable geometry with considerable mass in the 1300–1500 m elevation range, a retreat of the ELA to >1300 plausible within 25–40 years, could trigger runaway wastage.